From Theory To Practice: A Comprehensive Examination Of Implementing Project-Based Learning In STEM Curricula - Hasbullah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study undertook a comprehensive examination of Project-Based Learning (PBL) implementation in STEM curricula, bridging the gap from theory to practice. Through a rigorous exploration, the research aimed to investigate the practical implications of incorporating PBL into STEM education. The study's objectives were to assess the impact of PBL on academic performance, critical thinking skills, and overall Engagement among students in STEM disciplines. Utilizing a mixed-methods approach, including surveys, interviews, and observational analysis, data was collected and analyzed to provide a nuanced understanding of the experiences and outcomes associated with PBL. The findings revealed a significant improvement in academic performance, with students exposed to PBL exhibiting heightened Engagement and a notable surge in interest in STEM subjects. Critical thinking skills experienced substantial enhancement, highlighting the practical implications of PBL in developing essential cognitive abilities. The study contributed to the existing literature by validating the positive outcomes of PBL. It offered valuable insights for educators and curriculum developers seeking to implement effective, experiential learning strategies in STEM education. The research, conducted in the past tense, presents a comprehensive exploration of the transition from theoretical concepts to the practical application of PBL in STEM curricula.